Tract-based spatial statistical analysis (TBSS) of diffusion imaging in children with dyslexia : a secondary data analysis - Chu, Jermain Choy Ning (2018)
Existing diffusion studies on typically developing (TD) children and children with dyslexia have commonly studied the microstructural integrity of the left superior longitudinal fasciculus (SLF) using two diffusion tensor imaging (DTI) indexes: fractional anisotropy (FA) and mean diffusivity (MD). Least commonly used are axial diffusivity (AD) and radial diffusivity (RD). In addition, there is a lack of diffusion studies in dyslexia that have used tract-based spatial statistics (TBSS) to explore the relationship between behavioural measures (i.e. mean reading and verbal working memory scores) and multiple DTI indexes in the corpus callosum (CC) and cerebellum. The present study fills this research gap with the aim to investigate the relationships between the white matter microstructural integrity in the intrahemispheric, commissural and cerebellar tracts of TD children and children with dyslexia, with and without behavioural measures. Both groups when combined showed significant positive correlations between mean reading scores and (i) MD in the left SLF and CC; and (ii) FA, MD and AD in the right SLF. This finding suggests a possibility that the white matter microstructural integrity in the CC, right and left SLF develops across a continuum in TD children and children with dyslexia. To the best of our knowledge, this is the first DTI study that utilises TBSS to explore the differences and relationships in white matter microstructural integrity of commissural and cerebellar tracts, as well as behavioural measures in dyslexia. The significance of our current findings highlights the importance of using alternative methods of data collection and analysis to further explore the intrahemispheric, commissural and cerebellar tracts.